Dry-method electrode binder, preparation method thereof and electrode slice
By grafting acrylic copolymer on functionalized nanocarbon materials, an electrochemically stable dry electrode binder at the low potential of the negative electrode was prepared, which solved the problem of insufficient stability of PTFE under the negative electrode of lithium battery, improved the adhesion effect and battery capacity, and achieved a non-fluorinated environmentally friendly solution.
Patent Information
- Application Number
- CN202411789857.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
AI Technical Summary
Polytetrafluoroethylene (PTFE) is insufficient in stability under the negative electrode of lithium batteries, resulting in lithiation and consumption of active lithium and weakening the adhesion effect.
A dry electrode binder with an acrylic structure of saturated carbon chains ensures electrochemical stability at a negative electrode low potential by grafting the acrylic copolymer on a functionalized nanocarbon material.
It overcomes the problem of unstable potential in the negative electrode of PTFE, avoids lithium consumption, improves adhesion effect and battery capacity, and at the same time realizes a non-fluorinated, environmentally friendly solution.
Smart Images

Figure CN119674075A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a dry electrode binder and a preparation method thereof and an electrode sheet. Background Art
[0002] As an important component in lithium-ion batteries, the performance of electrode sheets greatly affects the performance of lithium-ion batteries.
[0003] The preparation methods of electrode sheets include wet process and dry process. Among them, the dry process abandons the use of solvents. By uniformly mixing the binder, active material and conductive agent by dry method, thicker electrodes can be prepared, while avoiding the problem of uneven distribution of binders. This process effectively improves the energy density and reduces production costs by increasing the thickness of the electrode. At present, polytetrafluoroethylene (PTFE) is the mainstream choice of dry electrode binder system. Its advantage is that it can undergo in-situ fiberization under the action of high temperature and high shear force, thereby effectively bonding the active material.
[0004] However, when PTFE is used in lithium battery systems, it lacks stability at low potentials and will undergo an irreversible reaction with lithium, resulting in lithiation and consumption of active lithium when used at the negative electrode, thereby weakening the adhesion effect. Summary of the invention
[0005] In order to solve the problem of poor adhesion of polytetrafluoroethylene when used for negative electrodes in the prior art, the present invention provides a dry electrode binder. The dry electrode binder adopts an acrylic acid structure with a saturated carbon chain, is electrochemically stable at low potential of the negative electrode, and solves the problem of poor adhesion of polytetrafluoroethylene when used for negative electrodes in the prior art.
[0006] The technical solution adopted by the present invention to solve its technical problem is: A dry electrode binder, wherein the active ingredients in the raw materials include the following components in parts by weight: 0.1~20 parts of functionalized nanocarbon material; 1 to 40.0 parts of ethylenically unsaturated carboxylic acid; 1 to 50.0 parts of unsaturated water-soluble monomer; 1 to 80.0 parts of unsaturated oil-soluble monomer; Emulsifier 0.1-20.0 parts; Initiator 0.1-10.0 parts; 1 to 40.0 parts of pH regulator; Wherein, the functionalized nano-carbon material is a nano-carbon material modified with carbon-carbon double bonds.
[0007] Optionally, the functionalized nanocarbon material is prepared according to the following method: The nano-carbon material is treated with mixed acid at 80-100° C. and then mixed with a silane surface modification auxiliary agent having a carbon-carbon double bond to react, thereby obtaining the functionalized nano-carbon material.
[0008] Optionally, the mass ratio of the nano-carbon material to the mixed acid is 1:(8-15).
[0009] Optionally, the nano-carbon material is graphene or carbon nanotubes.
[0010] Optionally, the ethylenically unsaturated carboxylic acid is selected from at least one of acrylic acid, itaconic acid, methacrylic acid, β-carboxyethyl acrylate, and fumaric acid.
[0011] Optionally, the unsaturated water-soluble monomer is selected from at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, acrylamide, methacrylamide, ethylene glycol vinyl ether, allyl hydroxyethyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, N-hydroxyethyl acrylamide, 2-acrylamido-2-methylpropane sulfonic acid, hydroxypropyl methacrylate, sodium vinyl sulfonate, and sodium p-styrene sulfonate.
[0012] Optionally, the unsaturated oil-soluble monomer is selected from at least one of styrene, acrylonitrile, methacrylonitrile, vinyl acetate, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, octyl methacrylate, isodecyl acrylate, isodecyl methacrylate, and phenyl acrylate.
[0013] Optionally, the pH adjuster is an inorganic base or an organic base.
[0014] Another object of the present invention is to provide a method for preparing the dry electrode binder as described above, comprising the following steps: S1: adding ethylenically unsaturated carboxylic acid, unsaturated water-soluble monomer, unsaturated oil-soluble monomer and emulsifier into pure water according to the formula amount to obtain a liquid component, and adding the liquid component into a premixing kettle with stirring; S2: dissolving the initiator in pure water according to the formula amount to prepare an initiator solution; S3: adding the functionalized nano-carbon material and pure water into a reactor according to the formula, starting stirring, deoxygenating, heating the liquid components in the reactor to 50-100° C., adding the initiator solution and the liquid components in the premixing reactor, and heat-insulating to obtain a modified acrylic polymer glue; S4: adding a pH adjuster to the modified acrylic polymer glue solution to adjust the pH to 3-9 to obtain a dry electrode binder solution; and drying the solution to obtain a dry electrode binder.
[0015] Another object of the present invention is to provide an electrode sheet comprising the dry electrode binder as described above.
[0016] The beneficial effects of the present invention are: The dry electrode binder provided by the present invention introduces functionalized nano-carbon materials into raw materials, and grafts acrylic copolymers onto the functionalized nano-carbon materials so that the binder adopts an acrylic structure with a saturated carbon chain, is electrochemically stable in the low potential of the negative electrode, and overcomes the problem that the potential of PTFE in the negative electrode is unstable, consumes lithium in the battery, and affects the adhesion effect and battery capacity; in addition, the dry electrode binder provided by the present invention is non-fluorinated and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0018] Figure 1 is a CV graph of a button cell prepared using the binder provided in Example 1 of the present invention; Figure 2 This is an EIS graph of a button cell prepared with the binder provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0019] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0020] Existing PTFE is unstable at low potentials, and when it is applied as a binder to the negative electrode of a lithium-ion battery, it easily accepts electrons and undergoes a side reaction to generate lithium fluoride, which consumes active lithium. This reaction not only weakens the bonding effect, but also causes a decrease in battery capacity.
[0021] In order to solve the problem of poor adhesion of polytetrafluoroethylene when used for negative electrodes in the prior art, the present invention provides a dry electrode binder, wherein the active ingredients in the raw materials include the following components in parts by weight: 0.1~20 parts of functionalized nanocarbon material; 1 to 40.0 parts of ethylenically unsaturated carboxylic acid; 1 to 50.0 parts of unsaturated water-soluble monomer; 1 to 80.0 parts of unsaturated oil-soluble monomer; Emulsifier 0.1-20.0 parts; Initiator 0.1-10.0 parts; 1 to 40.0 parts of pH regulator; Among them, the functionalized nanocarbon material is a nanocarbon material modified with carbon-carbon double bonds.
[0022] The dry electrode binder provided by the present invention introduces functionalized nano-carbon materials into raw materials, and grafts acrylic copolymers onto the functionalized nano-carbon materials so that the binder adopts an acrylic structure with a saturated carbon chain, is electrochemically stable in the low potential of the negative electrode, and overcomes the problem that the potential of PTFE in the negative electrode is unstable, consumes lithium in the battery, and affects the adhesion effect and battery capacity; in addition, the dry electrode binder provided by the present invention is non-fluorinated and environmentally friendly.
[0023] The functionalized nanocarbon material of the present invention is prepared according to the following method: The nano-carbon material is treated with mixed acid at 80-100°C and then mixed with a silane surface modification auxiliary agent having a carbon-carbon double bond to obtain a functionalized nano-carbon material.
[0024] The mixed acid of the present invention is preferably a mixture of concentrated nitric acid and concentrated sulfuric acid, wherein the mass concentration of the concentrated nitric acid is 68%, and the mass concentration of the concentrated sulfuric acid is 98%, and the mixed acid is preferably a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1.
[0025] The specific process of treating the nanocarbon material at 80-100°C by mixed acid is preferably as follows: adding the nanocarbon material to a mixed acid of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, heating it to 80-100°C in a reaction vessel with a reflux and stirring device, and keeping it warm for 3-8 hours for oxidation treatment. This treatment method can basically maintain the basic properties of the nanocarbon material and introduce an appropriate amount of oxygen-containing functional groups on its surface.
[0026] In order to take into account both the oxidation treatment effect and the economy, the present invention preferably has a mass ratio of the nano-carbon material to the mixed acid of 1:(8-15), and further preferably has a mass ratio of the nano-carbon material to the mixed acid of 1:10.
[0027] In order to ensure the conductivity of the dry electrode binder and reduce the internal resistance of the electrode, the present invention preferably uses graphene or carbon nanotubes as the nanocarbon material, and preferably the graphene has a diameter greater than 500nm and a number of layers less than 10; preferably the carbon nanotube has an aspect ratio greater than 500.
[0028] The present invention preferably mixes the oxidized nano-carbon material with a silane surface modification agent having a carbon-carbon double bond and reacts the mixture according to the following process: The nanocarbon material after the mixed acid treatment is separated by centrifugation or filtration and a large amount of residual acid is washed away with pure water; finally, the treated nanocarbon material is redispersed in water, and a silane surface modification agent with a carbon-carbon double bond is added to modify its surface, and a double bond group with polymerization ability is introduced to obtain a functionalized nanocarbon material; the preferred mass ratio of the silane surface modification agent to the nanocarbon material is (0.01-0.3):1.
[0029] In the present invention, the silane surface modification agent with a carbon-carbon double bond is preferably selected from at least one of vinyl trimethoxysilane A171 and γ-methacryloxypropyl KH-570.
[0030] In order to ensure the bonding performance of the dry electrode binder, the present invention preferably selects at least one of the ethylenically unsaturated carboxylic acid from acrylic acid, itaconic acid, methacrylic acid, β-carboxyethyl acrylate, and fumaric acid; preferably the unsaturated water-soluble monomer is selected from at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, acrylamide, methacrylamide, ethylene glycol vinyl ether, allyl hydroxyethyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, N-hydroxyethyl acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, hydroxypropyl methacrylate, sodium vinyl sulfonate, and sodium p-styrene sulfonate; preferably the unsaturated oil-soluble monomer is selected from at least one of styrene, acrylonitrile, methacrylonitrile, vinyl acetate, methyl acrylate, methyl At least one of methyl acrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, octyl methacrylate, isodecyl acrylate, isodecyl methacrylate, phenyl acrylate and lauryl methacrylate; preferably, the emulsifier is selected from one or more of anionic surfactants, nonionic surfactants and reactive surfactants; preferably, the initiator is selected from at least one of persulfates, hydroperoxides, organic peroxides, azo and redox initiators; preferably, the pH adjuster is an inorganic base or an organic base, specifically, preferably, the inorganic base is selected from at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide and ammonia water; preferably, the organic base is an alcoholamine organic base.
[0031] At present, the mainstream binder for dry electrodes is PTFE. The reason why PTFE has become the mainstream binder is that it can be fibrillated under high temperature and high shear, and contact and bond with active materials in the absence of solvents; in addition, the particle size of PTFE is large, resulting in limited bonding effect and easy to fall off during the cycle; at the same time, the increase in its internal resistance leads to aggravated polarization under large current. The present invention grafts long-chain acrylic copolymers on carbon nanotubes (CNT) or graphene, without high shear, and can realize the three-dimensional network structure of the electrode using existing lithium battery mixing equipment, while making the pole piece material have certain mechanical properties, solving the problem of higher equipment and energy consumption required for dry electrode preparation; in addition, CNT or graphene as a molecular skeleton enhances the conductivity of the material, reduces the internal resistance of the pole piece, and helps to slow down the polarization phenomenon; the binder of the present invention adopts a low Tg design, combined with polar functional groups such as carboxyl, hydroxyl, cyano, and amide, which can give full play to the intermolecular force and charge interaction, and has a good bonding effect with the active material.
[0032] The dry electrode binder provided by the present invention can be used for cathode and anode electrodes and is suitable for energy storage devices such as lithium batteries and supercapacitors.
[0033] Another object of the present invention is to provide a method for preparing the dry electrode binder as described above, the preparation method comprising the following steps: S1: Add ethylenically unsaturated carboxylic acid, unsaturated water-soluble monomer, unsaturated oil-soluble monomer and emulsifier into pure water according to the formula amount, use a mixer or homogenizer to mix the mixture of monomer and water into a uniform liquid component, and add it into a premixing kettle with stirring; S2: Dissolve the initiator in pure water according to the formula to prepare an initiator solution, preferably the mass concentration of the initiator solution is 0.1-10.0 wt.%; S3: adding functionalized nano-carbon materials and pure water to a reactor according to the formula amount, starting stirring, introducing nitrogen to deoxygenate, heating the liquid components in the reactor to 50-100° C., adding the initiator solution and the liquid components in the premixed reactor, preferably slowly adding the initiator solution and the liquid components in the premixed reactor to the reactor while reacting, maintaining the reaction temperature within a preset range, and after all components are added to the reactor, heat-insulating treatment, preferably heat-insulating treatment for 30-600 minutes, to obtain a modified acrylic polymer glue; S4: Adding a pH adjuster to the modified acrylic polymer glue to adjust the pH to 3-9 to obtain a dry electrode binder solution, preferably the solid content of the dry electrode binder solution is 5-40.0wt.%; drying the solution, preferably by spray drying or vacuum drying to control the moisture content to below 0.7%, to obtain a powdered dry electrode binder.
[0034] The preparation method of the dry electrode binder provided by the present invention has a simple preparation process; the prepared dry electrode binder has a functionalized nano-carbon material introduced into the raw material, and an acrylic acid copolymer is grafted onto the functionalized nano-carbon material so that the binder adopts an acrylic acid structure with a saturated carbon chain, is electrochemically stable in the low potential of the negative electrode, and overcomes the problem that the potential of PTFE in the negative electrode is unstable, consumes lithium in the battery, and affects the adhesion effect and battery capacity; and the dry electrode binder provided by the present invention is non-fluorinated and environmentally friendly.
[0035] Another object of the present invention is to provide an electrode sheet, which includes the dry electrode binder as described above.
[0036] The electrode sheet provided by the present invention adopts a dry electrode binder, in which a functionalized nano-carbon material is introduced into the raw material, and an acrylic copolymer is grafted onto the functionalized nano-carbon material so that the binder adopts an acrylic structure with a saturated carbon chain, and is electrochemically stable at a low potential of the negative electrode, thereby overcoming the problem that the potential of PTFE in the negative electrode is unstable, lithium in the battery is consumed, and adhesion effect and battery capacity are affected; moreover, the dry electrode binder provided by the present invention is non-fluorinated and environmentally friendly.
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0038] Example 1 S0: According to the weight percentage, 10.0 parts of CNT (aspect ratio 600) were added to 100.0 parts of a mixed acid of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, and the temperature was raised to 80°C in a reaction vessel with a reflux and stirring device, and the temperature was kept for 8 hours for oxidation treatment to introduce oxygen-containing functional groups; the treated CNT was then separated by centrifugation and washed with pure water for 3 times; finally, the treated CNT was redispersed in water, 0.5 parts of silane additive A171 were added and stirred thoroughly to obtain a functionalized nanocarbon material, i.e., a functionalized CNT dispersion.
[0039] S1: According to weight parts, 12.0 parts of acrylic acid, 10.0 parts of acrylamide, 10.0 parts of acrylonitrile, 60.0 parts of isooctyl acrylate, 1.8 parts of anionic emulsifier sodium lauryl sulfate and 0.5 parts of nonionic emulsifier OP-10 are added to 150.0 parts of pure water, and the monomers and water are mixed into a uniform premixed liquid by stirring, and then added to a premixing kettle with stirring; S2: Dissolve 1.2 parts of initiator ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S3: According to the weight percentage, 8.0 parts of functionalized nanocarbon material and 150.0 parts of pure water were added to the reactor, stirring was started, nitrogen was introduced for deoxygenation, the liquid components in the reactor were slowly heated to 80°C, and then the initiator solution and the liquid components in the premixed kettle were slowly added to the reactor while reacting, and the reaction temperature was maintained within the range of 80±2°C. After all the components were added to the reactor, the temperature was kept for 120 minutes to obtain a modified acrylic polymer glue solution; S4: According to the weight percentage, 6.2 parts of pH regulator sodium hydroxide are added to adjust the pH to 7.5 to obtain a dry electrode binder solution with a solid content of 20.0wt.%; the above solution is dried by spray drying to control the moisture content to less than 0.5% to obtain a powdered dry electrode binder. This dry electrode binder can be used to prepare a negative electrode plate through a dry process.
[0040] Example 2 S0: According to the weight percentage, 10.0 parts of CNT (aspect ratio 1000) were added to 100.0 parts of a mixed acid of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, and the temperature was raised to 90°C in a reaction vessel with a reflux and stirring device, and kept warm for 5 hours for oxidation treatment to introduce oxygen-containing functional groups; the treated CNT was separated by suction filtration and washed with pure water for 3 times; finally, the treated CNT was redispersed in water, 0.8 parts of silane additive KH-570 was added and stirred thoroughly to obtain a functionalized nanocarbon material, i.e., a functionalized CNT dispersion.
[0041] S1: According to the weight parts, 18.0 parts of methacrylic acid, 10.0 parts of 2-acrylamido-2-methylpropanesulfonic acid, 12.0 parts of hydroxyethyl acrylate, 7.0 parts of styrene, 45.0 parts of butyl acrylate, 1.5 parts of anionic emulsifier sodium dodecylbenzenesulfonate and 0.5 parts of nonionic emulsifier T-20 are added to 200.0 parts of pure water, and the monomers and water are mixed into a uniform premixed liquid by stirring, and then added to a premixing kettle with stirring; S2: Dissolve 1.5 parts of initiator sodium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S3: According to the weight percentage, 8.0 parts of functionalized nanocarbon material and 150.0 parts of pure water were added to the reactor, stirring was started, nitrogen was introduced for deoxygenation, the liquid components in the reactor were slowly heated to 85°C, and then the initiator solution and the liquid components in the premixed kettle were slowly added to the reactor while reacting, and the reaction temperature was maintained within the range of 85±2°C. After all the components were added to the reactor, the reaction was kept warm for 150 minutes to obtain a modified acrylic polymer glue solution; S4: According to the weight percentage, 10.8 parts of pH regulator lithium hydroxide are added to adjust the pH to 6.8 to obtain a dry electrode binder solution with a solid content of 18.0wt.%; the above solution is dried by spray drying to control the moisture content to less than 0.6% to obtain a powdered dry electrode binder. This dry electrode binder can be used to prepare a negative electrode plate through a dry process.
[0042] Example 3 S0: According to the weight ratio, 10.0 parts of graphene (diameter 1 micron, number of layers less than 8) are added to 100.0 parts of concentrated nitric acid and concentrated sulfuric acid in a mixed acid with a volume ratio of 3:1, and the temperature is raised to 85°C in a reaction vessel with a reflux and stirring device, and the temperature is kept for 6 hours for oxidation treatment to introduce oxygen-containing functional groups; the above-treated graphene is then separated by centrifugation and washed with pure water for 3 times; finally, the above-treated graphene is re-dispersed in water, 1.0 part of vinyltrimethylsilane is added and stirred thoroughly to obtain a functionalized nanocarbon material, i.e., a functionalized graphene dispersion.
[0043] S1: According to the weight parts, 4.0 parts of itaconic acid, 6.0 parts of sodium p-styrene sulfonate, 15.0 parts of hydroxypropyl acrylate, 10.0 parts of ethylene glycol vinyl ether, 6.0 parts of ethyl acrylate, 55.0 parts of lauryl methacrylate, 1.2 parts of anionic emulsifier sodium stearate and 0.4 parts of nonionic emulsifier S-20 were added to 180.0 parts of pure water, and the monomers and water were mixed into a uniform premix by stirring, and added to a premixing kettle with stirring; S2: Dissolve 1.5 parts of initiator ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S3: According to the weight percentage, 4.0 parts of functionalized nanocarbon material and 200.0 parts of pure water were added to the reactor, stirring was started, nitrogen was introduced for deoxygenation, the liquid components in the reactor were slowly heated to 75°C, and then the initiator solution and the liquid components in the premixed kettle were slowly added to the reactor while reacting, and the reaction temperature was maintained within the range of 75±2°C. After all the components were added to the reactor, the temperature was kept for 180 minutes to obtain a modified acrylic polymer glue solution; S4: According to the weight percentage, 2.8 parts of pH regulator sodium hydroxide are added to adjust the pH to 7.9 to obtain a dry electrode binder solution with a solid content of 15.0wt.%; the above solution is dried by spray drying to control the moisture content to less than 0.4% to obtain a powdered dry electrode binder. This dry electrode binder can be used to prepare a negative electrode plate through a dry process.
[0044] Example 4 S0: According to the weight ratio, 10.0 parts of graphene (diameter 1 micron, number of layers less than 8) are added to 100.0 parts of a mixed acid of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, and the temperature is raised to 85°C in a reaction vessel with a reflux and stirring device, and the temperature is kept for 6 hours for oxidation treatment to introduce oxygen-containing functional groups; the treated graphene is then separated by centrifugation and washed with pure water for 3 times; finally, the treated graphene is redispersed in water, 1.2 parts of vinyltrimethylsilane is added and stirred thoroughly to obtain a functionalized nanocarbon material, i.e., a functionalized graphene dispersion.
[0045] S1: According to the weight parts, 30.0 parts of acrylic acid, 15.0 parts of acrylamide, 14.0 parts of styrene, 35.0 parts of isodecyl acrylate, 1.2 parts of anionic emulsifier sodium dodecyl sulfate and 0.4 parts of nonionic emulsifier OP-20 are added to 160.0 parts of pure water, and the monomers and water are mixed into a uniform premixed liquid by stirring, and then added to a premixing kettle with stirring; S2: Dissolve 1.0 part of the initiator in pure water to prepare a 0.8 wt.% initiator solution; S3: According to the weight percentage, 6.0 parts of functionalized nanocarbon material and 120.0 parts of pure water were added to the reactor, stirring was started, nitrogen was introduced for deoxygenation, the liquid components in the reactor were slowly heated to 90°C, and then the initiator solution and the liquid components in the premixed kettle were slowly added to the reactor while reacting, and the reaction temperature was maintained within the range of 90±2°C. After all the components were added to the reactor, the reaction was kept warm for 100 minutes to obtain a modified acrylic polymer glue solution; S4: According to the weight percentage, 12.0 parts of pH regulator lithium hydroxide are added to adjust the pH to 5.7 to obtain a dry electrode binder solution with a solid content of 22.0wt.%; the above solution is dried by spray drying to control the moisture content to less than 0.7% to obtain a powdered dry electrode binder. This dry electrode binder can be used to prepare a negative electrode plate through a dry process.
[0046] Example 5 S0: According to the weight ratio, 10.0 parts of graphene (diameter 1 micron, number of layers less than 8) are added to 100.0 parts of concentrated nitric acid and concentrated sulfuric acid in a mixed acid with a volume ratio of 3:1, and the temperature is raised to 85°C in a reaction vessel with a reflux and stirring device, and the temperature is kept for 6 hours for oxidation treatment to introduce oxygen-containing functional groups; the above-treated graphene is then separated by centrifugation and washed with pure water for 3 times; finally, the above-treated graphene is re-dispersed in water, 1.5 parts of vinyltrimethylsilane are added and stirred thoroughly to obtain a functionalized nanocarbon material, i.e., a functionalized graphene dispersion.
[0047] S1: According to the weight parts, 20.0 parts of methacrylic acid, 15.0 parts of acrylamide, 40 parts of acrylonitrile, 3.0 parts of styrene, 15.0 parts of isooctyl acrylate, 0.8 parts of anionic emulsifier sodium lauryl sulfate and 0.2 parts of nonionic emulsifier T-40 are added to 150.0 parts of pure water, and the monomers and water are mixed into a uniform premixed liquid by stirring, and then added to a premixing kettle with stirring; S2: Dissolve 2.0 parts of initiator potassium persulfate-sodium bisulfite in pure water to prepare a 2.0 wt.% initiator solution according to weight percentage; S3: According to the weight percentage, 7.0 parts of functionalized nanocarbon material and 150.0 parts of pure water were added to the reactor, stirring was started, nitrogen was introduced for deoxygenation, the liquid components in the reactor were slowly heated to 70°C, and then the initiator solution and the liquid components in the premixed kettle were slowly added to the reactor while reacting, and the reaction temperature was maintained within the range of 70±2°C. After all the components were added to the reactor, the temperature was kept for 180 minutes to obtain a modified acrylic polymer glue solution; S4: According to the weight percentage, 9.1 parts of pH regulator sodium hydroxide are added to adjust the pH to 7.2 to obtain a dry electrode binder solution with a solid content of 20.0wt.%; the above solution is dried by spray drying to control the moisture content to less than 0.6% to obtain a powdered dry electrode binder. This dry electrode binder can be used to prepare a negative electrode plate through a dry process.
[0048] Comparative Example 1 This comparative example uses commercially available PTFE (Shanghai Lianjing ultra-high molecular weight PTFE dispersion) as a binder.
[0049] Comparative Example 2 S1: According to weight parts, 12.0 parts of acrylic acid, 10.0 parts of acrylamide, 10.0 parts of acrylonitrile, 60.0 parts of isooctyl acrylate, 1.8 parts of anionic emulsifier sodium lauryl sulfate and 0.5 parts of nonionic emulsifier OP-10 are added to 150.0 parts of pure water, and the monomers and water are mixed into a uniform premixed liquid by stirring, and then added to a premixing kettle with stirring; S2: Dissolve 1.2 parts of initiator ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S3: According to the weight percentage, 8.0 parts of CNT (aspect ratio 600) and 150.0 parts of pure water were added to the reactor, stirring was started, nitrogen was introduced for deoxygenation, the liquid components in the reactor were slowly heated to 80°C, and then the initiator solution and the liquid components in the premixed kettle were slowly added to the reactor while reacting, and the reaction temperature was maintained within the range of 80±2°C. After all the components were added to the reactor, the temperature was kept for 120 minutes to obtain a modified acrylic polymer glue solution; S4: According to the weight proportion, 6.2 parts of pH adjuster sodium hydroxide were added to adjust the pH to 7.5 to obtain a dry electrode binder solution with a solid content of 18.0 wt.%; the above solution was dried by spray drying to control the moisture content below 0.6% to obtain a powdered dry electrode binder.
[0050] Comparative Example 3 S0: According to the weight percentage, 10.0 parts of CNT (aspect ratio 600) were added to 100.0 parts of a mixed acid of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, and the temperature was raised to 80°C in a reaction vessel with a reflux and stirring device, and the temperature was kept for 8 hours for oxidation treatment to introduce oxygen-containing functional groups; the treated CNT was then separated by centrifugation and washed with pure water for 3 times; finally, the treated CNT was redispersed in water, 0.5 parts of silane additive A171 were added and stirred thoroughly to obtain a functionalized nanocarbon material, i.e., a functionalized CNT dispersion.
[0051] S1: According to the weight parts, 10.0 parts of acrylonitrile, 60.0 parts of isooctyl acrylate, 1.8 parts of anionic emulsifier sodium dodecylbenzene sulfonate and 0.5 parts of nonionic emulsifier OP-10 are added to 150.0 parts of pure water, and the monomers and water are mixed into a uniform premixed liquid by stirring, and then added to a premixing kettle with stirring; S2: Dissolve 1.2 parts of initiator ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S3: According to the weight percentage, 8.0 parts of functionalized nanocarbon material and 150.0 parts of pure water were added to the reactor, stirring was started, nitrogen was introduced for deoxygenation, the liquid components in the reactor were slowly heated to 80°C, and then the initiator solution and the liquid components in the premixed kettle were slowly added to the reactor while reacting, and the reaction temperature was maintained within the range of 80±2°C. After all the components were added to the reactor, the temperature was kept for 120 minutes to obtain a modified acrylic polymer glue solution; S4: Add 6.5 parts of pH regulator lithium hydroxide by weight, adjust the pH to 7.7, and obtain a dry electrode binder solution with a solid content of 16.0wt.%; dry the solution by spray drying, control the moisture content to below 0.7%, and obtain a powdered dry electrode binder. This dry electrode binder can be used to prepare a negative electrode sheet through a dry process.
[0052] Comparative Example 4 S0: According to the weight percentage, 10.0 parts of CNT (aspect ratio 600) were added to 100.0 parts of a mixed acid of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, and the temperature was raised to 80°C in a reaction vessel with a reflux and stirring device, and the temperature was kept for 8 hours for oxidation treatment to introduce oxygen-containing functional groups; the treated CNT was then separated by centrifugation and washed with pure water for 3 times; finally, the treated CNT was redispersed in water, 0.5 parts of silane additive A171 were added and stirred thoroughly to obtain a functionalized nanocarbon material, i.e., a functionalized CNT dispersion.
[0053] S1: According to the weight percentage, 82.0 parts of acrylic acid and 10.0 parts of acrylamide are added to 150.0 parts of pure water, and the monomers and water are mixed into a uniform premixed liquid by stirring, and then added into a premixing kettle with stirring; S2: Dissolve 1.2 parts of initiator ammonium persulfate in pure water to prepare a 1.0 wt.% initiator solution; S3: According to the weight percentage, 8.0 parts of functionalized nanocarbon material and 150.0 parts of pure water were added to the reactor, stirring was started, nitrogen was introduced for deoxygenation, the liquid components in the reactor were slowly heated to 80°C, and then the initiator solution and the liquid components in the premixed kettle were slowly added to the reactor while reacting, and the reaction temperature was maintained within the range of 80±2°C. After all the components were added to the reactor, the temperature was kept for 120 minutes to obtain a modified acrylic polymer glue solution; S4: According to the weight percentage, 37.5 parts of pH regulator sodium hydroxide are added to adjust the pH to 6.1 to obtain a dry electrode binder solution with a solid content of 15.0wt.%; the above solution is dried by spray drying to control the moisture content to less than 0.6% to obtain a powdered dry electrode binder. This dry electrode binder can be used to prepare a negative electrode sheet through a dry process.
[0054] The binders prepared in the above-mentioned embodiments and comparative examples were prepared into a negative electrode dry powder mixture, wherein the binder in comparative example 1 was prepared according to the following method: Artificial graphite, conductive agent SP and PTFE were mixed under high shear in a mass ratio of 96:1:3, with a mixing temperature of 180° C. and a shear time of 4 h to fiberize the PTFE and obtain a negative electrode dry powder mixture.
[0055] Except for Comparative Example 1, the binders in each embodiment and other comparative examples were prepared according to the following method: Artificial graphite, conductive agent SP and dry electrode binders prepared in Examples 1-5 and Comparative Examples 2-4 were wet dispersed and mixed in a mass ratio of 96:1:3, and a disperser was used to rotate at 800 rpm for 30 seconds and 2000 rpm for 10 minutes to uniformly disperse the slurry. The dispersed slurry was vacuum dried at room temperature to remove solvent moisture to obtain a negative electrode dry powder mixture.
[0056] The above negative electrode dry powder mixture is prepared into a dry electrode negative electrode sheet according to the following method: The negative electrode dry powder mixture obtained above was coated on the current collector copper foil and rolled at 70°C to form a dry electrode negative electrode sheet. A dry electrode negative electrode sheet with a thickness of 120 μm and uniform thickness was obtained by repeated rolling. The sheet peeling force was tested, and the peeling force test was carried out in accordance with GB / T 2792-2014; the test results are shown in Table 1.
[0057] Table 1 The dry electrode negative electrode sheets prepared as above were used to prepare batteries respectively: The dry electrode negative electrode plates prepared in Example 1 and Comparative Examples 1-4 were assembled with lithium metal plates into lithium ion button cells, and LiPF6 was dissolved in an electrolyte of EC / DEC / EMC=2:3:1 at a concentration of 1 mol / L. After the button cell assembly was completed, EIS and initial efficiency were tested, wherein the EIS of Example 1 showed Figure 2 The initial effects of Examples 1-5 and Comparative Examples 1-4 are shown in Table 2.
[0058] Table 2 sample First charge specific capacity mAh / g First discharge specific capacity mAh / g First effect% Example 1 365.3 390.4 93.56 Example 2 363.7 390.2 93.21 Example 3 370.5 392.6 94.37 Example 4 364.2 389.5 93.5 Example 5 343.8 380.5 90.36 Comparative Example 1 307.9 358.9 85.79 Comparative Example 2 304.5 364.0 83.65 Comparative Example 3 301.7 365.5 82.54 Comparative Example 4 284.4 357.7 79.51 The CV sample preparation process is as follows: The binder prepared in Example 1 was mixed with carbon black at a ratio of 1:1 and coated on a copper foil. LiPF6 was dissolved in an electrolyte solution of EC / DEC / EMC=2:3:1 at a concentration of 1 mol / L and assembled into a button cell. The CV of Example 1 was tested. Figure 1 shown.
[0059] It can be seen from the above data that the dry electrode binder provided by the present invention does not require high shearing during use and has low requirements on equipment; at the same time, it has good adhesion and high conductivity, which helps to slow down polarization.
[0060] The PTFE in Comparative Example 1 requires high shearing during use, has high requirements on equipment, and has poor adhesion. When used for the negative electrode, it has poor peeling force and low initial efficiency.
[0061] The difference between Comparative Example 2 and Example 1 is that the CNTs are not subjected to functionalization treatment, and the adhesiveness and electrochemical performance of the obtained binder are reduced.
[0062] The difference between Comparative Example 3 and Example 1 is that no unsaturated water-soluble monomer is added, and the adhesiveness of the obtained binder is reduced, and the electrochemical first effect is also reduced.
[0063] The difference between Comparative Example 4 and Example 1 is that the unsaturated oil-soluble monomer is replaced with an ethylenically unsaturated carboxylic acid. When the obtained adhesive is subjected to a peel strength test, the powder falls off severely and the test cannot be performed. At the same time, the electrochemical first effect is significantly reduced.
[0064] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A dry electrode binder, characterized in that: The active ingredients in the raw materials include the following components in parts by weight: 0.1~20 parts of functionalized nanocarbon material; 1 to 40.0 parts of ethylenically unsaturated carboxylic acid; 1 to 50.0 parts of unsaturated water-soluble monomer; 1 to 80.0 parts of unsaturated oil-soluble monomer; Emulsifier 0.1-20.0 parts; Initiator 0.1-10.0 parts; 1 to 40.0 parts of pH regulator; Wherein, the functionalized nano-carbon material is a nano-carbon material modified with carbon-carbon double bonds.
2. The dry electrode binder according to claim 1, characterized in that: The functionalized nano-carbon material is prepared according to the following method: The nano-carbon material is treated with mixed acid at 80-100° C. and then mixed with a silane surface modification auxiliary agent having a carbon-carbon double bond to react, thereby obtaining the functionalized nano-carbon material.
3. The dry electrode binder according to claim 2, characterized in that: The mass ratio of the nano-carbon material to the mixed acid is 1:(8-15).
4. The dry electrode binder according to claim 2, characterized in that: The nano carbon material is graphene or carbon nano tube.
5. The dry electrode binder according to claim 1, characterized in that: The ethylenically unsaturated carboxylic acid is selected from at least one of acrylic acid, itaconic acid, methacrylic acid, β-carboxyethyl acrylate, and fumaric acid.
6. The dry electrode binder according to claim 1, characterized in that: The unsaturated water-soluble monomer is selected from at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, acrylamide, methacrylamide, ethylene glycol vinyl ether, allyl hydroxyethyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, N-hydroxyethyl acrylamide, 2-acrylamido-2-methylpropane sulfonic acid, hydroxypropyl methacrylate, sodium vinyl sulfonate, and sodium p-styrene sulfonate.
7. The dry electrode binder according to claim 1, characterized in that: The unsaturated oil-soluble monomer is selected from at least one of styrene, acrylonitrile, methacrylonitrile, vinyl acetate, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, octyl methacrylate, isodecyl acrylate, isodecyl methacrylate, and phenyl acrylate.
8. The dry electrode binder according to claim 1, characterized in that: The pH adjuster is an inorganic base or an organic base.
9. A method for preparing a dry electrode binder according to any one of claims 1 to 8, characterized in that: The steps include: S1: adding ethylenically unsaturated carboxylic acid, unsaturated water-soluble monomer, unsaturated oil-soluble monomer and emulsifier into pure water according to the formula amount to obtain a liquid component, and adding the liquid component into a premixing kettle with stirring; S2: dissolving the initiator in pure water according to the formula amount to prepare an initiator solution; S3: adding the functionalized nano-carbon material and pure water into a reactor according to the formula, starting stirring, deoxygenating, heating the liquid components in the reactor to 50-100° C., adding the initiator solution and the liquid components in the premixing reactor, and heat-insulating to obtain a modified acrylic polymer glue; S4: adding a pH adjuster to the modified acrylic polymer glue solution to adjust the pH to 3-9 to obtain a dry electrode binder solution; and drying the solution to obtain a dry electrode binder.
10. An electrode sheet, characterized in that: It comprises the dry electrode binder as described in any one of claims 1 to 8.
Citation Information
Cited By
Lithium iron phosphate dry-method electrode plate and preparation method thereof
CN119864369A
A dry-type lithium iron phosphate electrode sheet and a preparation method thereof
CN119864369B